Portugal : Staff Report for the 2015 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Portugal's significant flow imbalances have largely been corrected in the wake of the sovereign debt crisis, with employment increasing, output expanding, and the current account balance posting surpluses for the first time in decades. The economy has expanded at close to 1 percent per year on average since early 2013, with growth driven largely by consumption. The near-term outlook is benefiting from the trifecta of record-low interest rates, a weakening euro, and low oil prices. Output is expected to increase by 1.6 percent in 2015 and by 1.5 percent in 2016, with outlook for inflation improving as well.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet